JAK2 mutation and treatment of JAK2 inhibitors in Philadelphia chromosome-negative myeloproliferative neoplasms - Hutajulu, Susanna Hilda; Kurnianda, Johan (Acta Interna The Journal of Internal Medicine, 2013)
ABSTRACTThe Philadelphia chromosome-negative (Ph-negative) myeloproliferative neoplasms (MPNs) polycythaemia vera (PV), essential thombocythaemia (ET) and primary myelofi brosis (PMF) are clonal disorders of multipotent haematopoietic progenitors. The genetic cause of these disorders was not fully defi ned until a somatic activating mutation in the JAK2 non-receptor tyrosine kinase, JAK2V617F, was identifi ed in most patients with PV and a considerable proportion of patients with ET and PMF. The discovery of JAK2 mutation has changed the molecular reclassification of MPNs and served as a genomic target for therapeutic implication. A number of JAK2 inhibitors have been developed and tested for MPNs. Several JAK2 inhibitors have reached the phases of clinical trial and included patients with intermediate-risk or high-risk MF. This population of MF is the best candidate for trials because currently it has no effective therapy besides patientsâ poor survival. Considering all clinical data on Ph negative MPNs, JAK2 inhibitors have shown a clinical benefi t and reduced symptoms in the vast majority of MF cases. The most developed among JAK2 inhibitors is Ruxolitinib, which has demonstrated clinical improvement with well tolerated toxicities. However, JAK2 inhibitor was equally active in patients with and without JAK2 mutation. Other JAK2 inhibitors are less developed, but showed a similar clinical benefi t. Furthermore, its effect on the natural course of MPNs in treating patients needs to be investigated.Keywords: myeloproliferative neoplasms â JAK2 mutation â JAK2 inhibitors.